Chlortetracycline degradation performance and mechanism in the self-biased bio-photoelectrochemical system constructed with an oxygen-defect-rich BiVO4/Ni9S8 photoanode. (May 2022) - Tu, Lingli; Rong, Yiyuan; Yu, Zebin; Chen, Shuo; Sun, Jiangli; Li, Zhihong; Li, Jialu; Hou, Yanping
Abstract: Efficient photoelectrodes are highly desired in bio-photoelectrochemical systems (BPES). Herein, in this paper, the oxygen defect-rich BiVO4 /Ni9 S8 photoanode was developed and coupled with a biocathode for enhanced chlortertracycline (CTC) degradation and current generation in the self-biased BPES. Characterization results showed that the optimized BiVO4 /Ni9 S8 -7 mg-150 °C NF exhibited the best photocatalytic activity, due to that the rich oxygen vacancies and Ni9 S8 could significantly improve light absorption, enhance photo-generated carriers separation, and accelerate charges transfer. CTC (20 mg L −1 ) removal efficiency from the BPES was about 1.3 times (82.3% vs 64.7%) of that from the unilluminated reactor, and current output (0.68 A m −3 ) was about 7.6 times (0.09 A m −3 ). The dominant species in genus level was Geobacter, which is capable of reducing nitroaromatics and in favor of reductive dehalogenation of CTC. Besides, Comamonas and Rhodopseudomonas that are capable of degrading antibiotics were also detected. Possible degradation pathways and mechanism of CTC degradation in the BPES were proposed. This research advances the development of photoelectrode materials for light-driven BPESs and enriches antibiotics degradation mechanism. Graphical abstract: Image 1 Highlights: BPESs with BiVO4 /Ni9 S8 photoanode and biocathode was developed for CTC removal. Oxygen vacancy and Ni9 S8 could improve photocatalytic activity of the photoanode. Geobacter and species capable of degrading antibiotic were detected on biocathode. Possible CTC degradation pathways and mechanism were proposed.